Evaluation of triethanolamine‑cashew nutshell liquid derivatives as crude oil emulsion breakers - Victor‑Oji, C. O.; Chukwu, U. J.; Akaranta, O. (Applied Petrochemical Research, 2021)
Three bio-based crude oil emulsion breakers have been prepared from agricultural waste by chemical treatment of cashew nutshell liquid (CNSL) extract with triethanolamine via a one-pot reaction at 120 ℃. The triethanolamine-ester deriva tives were characterized by Fourier Transform–InfraRed spectroscopy. Their efectiveness as crude oil emulsion breakers were investigated experimentally using the bottle test method. The efect of solvent type, water content, and concentration of the emulsion breaker, was used to study the demulsifcation process and determine their demulsifcation efciency at a temperature of 60 ℃ for a contact time of 180 min. A commercial demulsifer, PhaseTreat 4633 (PT-4633) was used as a benchmark. Performance evaluation of the prepared emulsion breakers revealed their efectiveness in descending order as: triethanolamine dianacardate (TED)>triethanolamine trianacardate (TET)>triethanolamine anacardate (TEA). The data reveals that their emulsion breaking efciency increases with increasing emulsion water content, and concentration. PT-4633 exhibited better demulsifcation efciency than the triethanolamine-esters in xylene across the concentration and water con tent studied. Improved water separation was however observed for the triethanolamine-esters in butanol, as triethanolamine trianacardate (TET) performed better than PT-4633 at 10 ppm to 20 ppm at 30% water content with a water separation of 83.33% and 80% respectively. The evaluated triethanolamine ester derivatives exhibited better emulsion breaking potentials in butanol than xylene at shorter times, which may be due to the synergistic efect of butanol. Therefore, butanol could be used as a sustainable solvent substitute for xylene in demulsifer formulations.
Keywords: Cashew nutshell liquid (CNSL); Cashew nutshell liquid-triethanolamine esters; Crude oil emulsion; Demulsifers; Emulsion breakers; CFOREM; Université de Ouaga; ACE: Training, Research and Expertise in Drug Sciences